VALIDITY AND RELIABILITY OF LEARNING MOTIVATION INSTRUMENT (I-MABAR) STUDENTS IN ONLINE LEARNING DURING COVID 19 - Bachrizal Bakhtiar (Jurnal PPI Dunia, 2022)
This article aims to determine the validity of the construction and reliability of a learning motivation instrument (I-MABAR) of students in the time of covid pandemic 19. Researchers used a pilot study on 36 students of Universiti Pendidikan Sultan Idris (UPSI) as a sample to obtain reliability, and three supervisors to obtain validity. Researchers have developed a questionnaire with a google form that contains a total of 24 items. Student learning motivation should be measured to ensure the level of student learning motivation in the learning process in the current Covid-19 dememic. For that, there needs to be a learning motivation instrument that has a good degree of validity and reliability to get the right display of student learning motivation. The findings of the study show that 24 instrument items from the five main constructs of I-MABAR have a very high total item correlation value. However, there are two total instrument items that have a strong correlation value namely items D3 and E1. But all items have an acceptable validity value. While the findings of reliability values ​​using Cronbach Alpha analysis have a very high value. Thus, the validity and reliability of the instrument shows that the student learning motivation instrument (I-MABAR) has a quality that can be used to measure learning motivation.